Traditional and complementary treatments among Malay, Chinese and Indian chronic diseases: a systematic review - Yusoff, Salihah; Hassan, Siti Aishah; Wan Othman, Wan Norhayati (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Although the modern medicine has progressed for a long time, there are empirical studies shows the effectiveness of traditional and complementary treatments (TCT) in curing chronic diseases. In Malaysia, TCT is often related to the use of herbs and meditation that vary according to ethnicity. Each ethnic group has its own beliefs system in curing diseases. This study mainly aims to provide an overview on the perceptions of the effectiveness TCT in curing chronic diseases. The authors used electronic database to select 10 journal articles according to inclusion and exclusion criteria. Findings show the highest statistic among Sabah natives and followed by Malay ethnic on believing in the effectiveness of TCT. Price and encouragement from family and friends are the main influencing factors of taking TCT. We suggest that counsellors need to be aware of the TCT practices on particular culture in order to increase respect and trust in the helping relationships.